(untitled) (Journal of Geography and Environmental Management, 2023)
In this study, a geographical analysis of wind meteorology indicators and land topography was conducted to determine the most suitable wind farm locations in Azerbaijan. Long-term wind meteorological gauge data, satellite data, and advanced meteorological modelling were used to characterize wind energy potential nationwide. This data includes measurements of wind speed, direction, and turbulence collected over an extended period. Then, Geographic Information Systems (GIS) tools were used to evaluate the wind farms in terms of topography, ecology, and economy and to place edges around the restriction areas. The analysis results identified several areas with high wind energy potential, including the Caspian Sea coast, Absheron-Khizi, and the East Zangezur economic rayon. This analysis reveals the profound impact of terrain on wind flow dynamics and highlights the importance of considering local topography in site selection. Areas with consistent and strong winds, often associated with mountain passes and coastal areas, are identified as prime areas for wind energy development. The study also evaluates the proximity of these promising locations to the existing power grid. It is aimed at ensuring efficient energy transmission by evaluating the cost-effectiveness of connecting potential wind power plant sites to the grid. This grid integration assessment guides decisions regarding selected locations’ feasibility and economic viability.